化简:3/4X^2Y-[1/2XY+1/2(1/2X^2-9XY)]

来源:学生作业帮助网 编辑:作业帮 时间:2017/11/25 08:04:05
XY(XY+3)+(XY+4)+4(X+Y+1)-(X+Y+2)

XY(XY+3)+(XY+4)+4(X+Y+1)-(X+Y+2)XY(XY+3)+(XY+4)+4(X+Y+1)-(X+Y+2)XY(XY+3)+(XY+4)+4(X+Y+1)-(X+Y+2)XY(X

计算3xy[2xy-x(y-2)+x-1]

计算3xy[2xy-x(y-2)+x-1]计算3xy[2xy-x(y-2)+x-1]计算3xy[2xy-x(y-2)+x-1]3xy[2xy-x(y-2)+x-1]=3xy(2xy-xy+2x+x-1

化简!1、(x^2-xy)+xy+y^2 2、3(x^2-xy)-xy+y^2

化简!1、(x^2-xy)+xy+y^22、3(x^2-xy)-xy+y^2化简!1、(x^2-xy)+xy+y^22、3(x^2-xy)-xy+y^2化简!1、(x^2-xy)+xy+y^22、3(

化简 2(xy-xy²+3)-(-4xy²+xy-1) 其中,x等于--4,y等于-3

化简2(xy-xy²+3)-(-4xy²+xy-1)其中,x等于--4,y等于-3化简2(xy-xy²+3)-(-4xy²+xy-1)其中,x等于--4,y等于

.(x+y-2)(x+y-2xy)+(xy-1)^2

.(x+y-2)(x+y-2xy)+(xy-1)^2.(x+y-2)(x+y-2xy)+(xy-1)^2.(x+y-2)(x+y-2xy)+(xy-1)^2令x=1得f(x,y)=0;知有因式(x-1

(x+y)(x+y+2xy)+(xy+1)(xy-1)(x+y)(x-y)+4(y-1)

(x+y)(x+y+2xy)+(xy+1)(xy-1)(x+y)(x-y)+4(y-1)(x+y)(x+y+2xy)+(xy+1)(xy-1)(x+y)(x-y)+4(y-1)(x+y)(x+y+2x

xy(xy+1)+xy+3-2(x+y+1/2)-(x+y-1)^2因式分解

xy(xy+1)+xy+3-2(x+y+1/2)-(x+y-1)^2因式分解xy(xy+1)+xy+3-2(x+y+1/2)-(x+y-1)^2因式分解xy(xy+1)+xy+3-2(x+y+1/2)

(-1/3xy)^2•[xy(2x-y)-2x(xy-y^2)]

(-1/3xy)^2•[xy(2x-y)-2x(xy-y^2)](-1/3xy)^2•[xy(2x-y)-2x(xy-y^2)](-1/3xy)^2•[xy(2x-

(-3分之1xy)的平方×[xy(2x-y)-2x(xy-y的平方)]

(-3分之1xy)的平方×[xy(2x-y)-2x(xy-y的平方)](-3分之1xy)的平方×[xy(2x-y)-2x(xy-y的平方)](-3分之1xy)的平方×[xy(2x-y)-2x(xy-y

1-2/x+y=xy,4y+6x=xy.求xy的解?

1-2/x+y=xy,4y+6x=xy.求xy的解?1-2/x+y=xy,4y+6x=xy.求xy的解?1-2/x+y=xy,4y+6x=xy.求xy的解?1-(2/x)+y=4y+6x1-(2/x)

若x-y=4,xy=1,求(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值

若x-y=4,xy=1,求(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值若x-y=4,xy=1,求(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值若x

(-2xy+2x+5y)-(3xy+2y-2x)-(x+4y+xy)其中x-y=4xy=-1

(-2xy+2x+5y)-(3xy+2y-2x)-(x+4y+xy)其中x-y=4xy=-1(-2xy+2x+5y)-(3xy+2y-2x)-(x+4y+xy)其中x-y=4xy=-1(-2xy+2x

x-y=1,xy=2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值

x-y=1,xy=2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值x-y=1,xy=2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值x-

.已知:x-y=1,xy=-2.求:(-2xy+2 x+3y)-(3xy+2y-2x)-(x+4y+xy)的值

.已知:x-y=1,xy=-2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+4y+xy)的值.已知:x-y=1,xy=-2.求:(-2xy+2x+3y)-(3xy+2y-2x)-(x+

若x-y=4,xy=1,则(2x+y-2xy)-(3x+2y+xy)-(4xy+3y-5x)=

若x-y=4,xy=1,则(2x+y-2xy)-(3x+2y+xy)-(4xy+3y-5x)=若x-y=4,xy=1,则(2x+y-2xy)-(3x+2y+xy)-(4xy+3y-5x)=若x-y=4

(-xy^-1)^2*(-xy^-2)^-3/(-x^2y^3)

(-xy^-1)^2*(-xy^-2)^-3/(-x^2y^3)(-xy^-1)^2*(-xy^-2)^-3/(-x^2y^3)(-xy^-1)^2*(-xy^-2)^-3/(-x^2y^3)这很简单

y^3+xy^2+2xy+x^2-1 因式分解

y^3+xy^2+2xy+x^2-1因式分解y^3+xy^2+2xy+x^2-1因式分解y^3+xy^2+2xy+x^2-1因式分解y^3+xy^2+2xy+x^2-1=(x+y-1)(x+y^2+y

5x^2y/-1/2xy*3xy^2

5x^2y/-1/2xy*3xy^25x^2y/-1/2xy*3xy^25x^2y/-1/2xy*3xy^25x^2y/-1/2xy*3xy^2=-7.5x²y²

( )-(x^2+3xy)=-xy-1/3y^2

()-(x^2+3xy)=-xy-1/3y^2()-(x^2+3xy)=-xy-1/3y^2()-(x^2+3xy)=-xy-1/3y^2()-(x^2+3xy)=-xy-1/3y^2()=(x^2+